100 Anniversary of State Establishment "Institute of Traumatology and Orthopedics of National Academy of Medical Sciences of Ukraine" - Bezrukhenko, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
In 2019, the Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine celebrates its 100th anniversary. This is an outstanding event, which marks an important stage in the formation and development of orthopedics and traumatology in our country.